Prehospital Cold-Water Immersion for Undifferentiated Heat Stroke: A Case Series - David Lindow; Bryan Everitt; Nick Smith; Michael Wells; Robert Dickson; Casey Patrick (Clinical Practice and Cases in Emergency Medicine, 2026)
Introduction: Heat stroke is a time-sensitive condition that requires early intervention to prevent morbidity and mortality. Heat-related deaths are also increasing. Multiple studies have evaluated various cooling methods and assessed their effectiveness, safety, and practicality across diverse settings and populations. Earlier and faster cooling leads to improved patient outcomes. The National Association of Emergency Medical Services Physicians recommends initiating prehospital cold-water immersion before emergency medical services (EMS) transport. Case Series: This case series evaluated the feasibility and effectiveness of prehospital cold-water immersion initiated before and continued during EMS transportation from the scene to emergency department arrival in this critically ill patient population. Conclusion: Rapid initiation and maintenance of prehospital cold-water immersion in undifferentiated heat stroke was both feasible and effective. Over the course of the case series, no deaths were reported, and all patients were eventually discharged home.